(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
Effective communication is vital for any business professional. Effective communication skills not only help to share ideas with others but they also foster good relationships among employees. Whether it is verbal or non-verbal communication both have equal importance. Therefore, keeping in mind the relevance of this subject for students, the present study was conducted. The study aimed to find management students’ perceptions regarding the importance of business communication course. This article discusses the problems in the development of professional communication in a foreign language of management students of non-philological higher education institutions and the ideas expressed for its solution. Non-philological higher education institutions ensure their rapid intellectual development, in-depth, specialized teaching, taking into account the interests and abilities of management students.